Map of part of the province of Manitoba and North West Territories shewing the Hudsons Bay Company's sections [part 2] - Dennis, John Stoughton (Surveyor); Burland Lithographic Company (Lithographer) (Hudson's Bay Company, 1881)
This is a map of land distribution in Manitoba and the Northwest Territories in 1881. It consists of two parts: part 1 - general map of the region; and part 2 - inset maps of major cities and towns, as well as Hudson's Bay Company's information on cities, farming, lands, climate, municipal organization, schools, timber and fuel industries, transportation and communication in Manitoba and the Northwest Territories [see also record for part 1]. Insets: Plan of the town plot of Goschen, Prince Albert, N.W.T. -- Plan of the H.B.Co's reserve Portage La Prairie, Manitoba -- Plan of Elphinstone, Manitoba -- Plan of West Lynne in the parish of St Agathe, Manitoba -- Plan of the town plot of Rosemount -- Plan of the H.B.Co's reserve Winnipeg, Manitoba -- Rat Portage Keewatin -- Plan of Colville -- Edmonton, North West Territory. Lots numbered. Includes information on cities, farming, lands, climate, municipal organization, schools, timber and fuel industries, transportation and communication in the region. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Scale not given.